Murder in the quran and sunnah (a study of causes effects and prevention) - Chasib ghazi rashak ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Man was created for the sake of survival, and therefore he attains advancement and a high level, as God Almighty made him a caliph (I will make you a caliph on earth), the caliph due to the capabilities he possesses that qualifies him over the rest of creation, as God said (and We honored the children of Adam), that honor due to the qualities and virtues bestowed upon him, and he deserves to be with them. A caliph is respected and honored because through him the lineage is preserved and honor is preserved. Therefore, God granted him the right to live life with dignity and freedom, and no one has the right to rob this creature dear to God of his dignity and freedom in life. Therefore, it is considered that taking any soul is the death of all human beings, and that keeping this soul alive is a life for all mankind (and whoever kills a soul for other than a soul, it is as if he had killed all mankind, and whoever saves a life, it is as if he had saved all mankind).Therefore, killing a human being is considered one of the most heinous crimes punishable by law, whether intentionally or accidentally. Accordingly, the taking of a human life falls under the afterlife punishment that God has warned against and promised its perpetrator hell. For this reason, the Holy Qur’an and Sunnah have warned in verses and hadiths against this criminal act, and this phenomenon is undesirable because it involves the dispersal of human society and the spread of chaos and revenge that lead to the spread of transgression and dissolution in society.In this research, we discuss killing in the Qur’an and Sunnah, a study of the causes and effects, where we review the most important reasons that lead to killing, including religious weakness, faith, temptation, envy, mental and nervous influences, and anger.... We also review the most important effects resulting from killing, including the wrath of God Almighty and the Messengers, the disappearance of life, and the annihilation of creation and offspring. And sins and eternity in hellfire... in addition to discussing the most important ways to prevent murder by following legitimate and legal methods such as retribution for the perpetrator and precaution in sparing blood, which contributes to reducing chaos and spreading societal security.